THE PROBLEM OF STRESS IN MODERN SOCIETY AND ITS PSYCHOPHYSIOLOGICAL CONSEQUENCES (American Journal of Interdisciplinary Research and Development, 2026)
This article examines the phenomenon of stress in modern society, the causes of its occurrence, and the psychological and physiological effects on the human body. The types of stress are analyzed, including short-term (eustress) and long-term (distress) forms. In addition, stress management methods and prevention methods are scientifically described. The results of the study show that integrated approaches are effective for reducing stress levels.